Presence of roughtail stingray Bathytoshia centroura (Elasmobranchii: Myliobatiformes: Dasyatidae) in the Southeastern Gulf of Mexico - Wakida-Kusunoki, Armando T.; Hernández-Lazo, Chrystian C.; Mendoza-Carranza, Manuel (Revista de Biología Marina y Oceanografía, 2018)
A Bathytoshia centroura female of 181 cm disk width was found during the monitoring of small scale fishery in the state of Tabasco, Mexico. The specimen was caught by a gill net vessel at 32 km northeastern of the port of Sanchez Magallanes, at 78 m depth. Large size and spacing of mid-dorsal bucklers, conspicuous tubercles on the outer parts of disc and tail with numerous rows of small spines were used to verify the identification. The presence of this species in the southeast of the Gulf of Mexico is reported, increasing up to five, the number of the species of the subfamily Dasyatinae in this zone.